Caminhos da formação tecnológica a distância: a complexidade emergente no desenho de curso de licenciatura - Pitombeira, Cátia Veneziano (2013)
This research aims to describe and interpret the phenomenon technology formation enabled by the Language Teaching Technologies class which is part of an undergraduate Language and Literature distance course on Portuguese/Spanish at a confessional university in the State of São Paulo, in order to identify the formation perceived by the students and the emerging traces of complexity, given the moment of paradigm transition lived by the researcher when designing the mentioned class. The research development was based on the complex thinking epistemology (Morin, 2002, 2007, 2008, 2011; Moraes, 2002,2004), articulated with education and teacher formation theories (Freire, 2002, 2008), and with issues regarding teacher technological education from the perspective of Lopes (2005) and Moraes (2007), connected to different visions of instructional design according to Moraes (2008), Graves (2000), and Freire (2013). The Hermeneutic-Phenomenological methodological approach (van Manen, 1990; Freire, 1998, 2007, 2008, 2012) was adopted and the research instruments were part of the class activities: Students from the 5th semester (a) participated in the Class-Activity Forum which preceded a videoclass; (b) answered a Teaching Practice Questionnaire from which was possible to draw their profile and collect their impressions about their performance and about the proposed activities; and (c) produced a dissertative-reflexive report. These written texts represent the participants registers on how they have been living the phenomenon on focus while unveiling the way they interpret the life experience they have been involved in, as suggested by the methodology that supports this study. The interpretation of the texts revealed the participants' reflection about technology formation, as well as about the course design, providing the teacher-researcher with moments of reflection upon the development of new online technological education courses, and the creation and elaboration of courses under the perspective of complexity